Evaluación de la mineralización del nitrógeno en un suelo ácido bajo fertilización inorgánica y orgánica - Torres Lozada, Luz Karime; Escobar Medina, Duvan; Soto Paz, Jonathan; Daza Torres, Martha Constanza; Torres Lozada, Patricia (Ingeniería, 2021)
Context: The population increase and the demand for food generate greater demands on productivity, which stimulates the use of inorganic fertilizers as a common practice in agricultural systems, thus generating potential risks of contamination by nutrient leaching, in addition to high costs that can affect the profitability of production systems. The application of organic materials from the composting of organic substrates is a common source of fertilization in clean, organic production systems with lower costs. Method: This study evaluated the effect of fertilization with an Organic Amendment (EO) from the composting of Municipal Biowaste-BW mixed with cachaça on the mineralization of nitrogen (Nmineralized) in an acidic soil through six treatments: three controls (T1: 100% soil; T2: 100% EO; T3: 100% ureainorganic fertilization: F) and three EO( %):F( %) proportions (T4: 50-50, T5: 75-25, T6: 25-75) during an incubation period of 16 weeks. Results: Four mineralization models were applied (Stanford & Smith, Broadbent, linear, and polynomial Exponential), and it was found that T4 allowed to achieve a contribution of Nmineralized (12.546,39 mg/kg) similar to inorganic fertilization (T3: 13.931,05 mg/kg); the Broadbent (R2 >0,98) and linear (R2 >0,90) models achieved the best fit. Conclusions: This partial inorganic fertilizer replacement strategy can achieve up to 50% inorganic fertilizer replacement.